The effect of industry, region and time on new business survival: A multi-dimensional analysis - Michael Fritsch; Udo Brixy; Oliver Falck (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2004)
We analyze the effect of industry, region and time on new-business survival rates by means of a multi-dimensional approach. The data relate to West German districts in the 1983-2000 period. The survival chances of start-ups tend to be relatively low in industries characterized by a high minimum efficient size and high numbers of entries. Regional growth has a rather pronounced positive influence on survival rates, while the relationship between the nationwide development of the particular industry and survival tends to be negative. We also find a remarkably high level of spatial autocorrelation. – – Wir analysieren den Einfluss von branchenspezifischen Faktoren und Standortein-flüssen über die Zeit auf die Überlebensraten neu gegründeter Betrieben mit ei-nem multidimensionalen Ansatz. Die Untersuchung bezieht sich auf die Kreise Westdeutschland im Zeitraum 1983-2000. Die Überlebenschancen sind relativ niedrig in Branchen, die durch eine hohe mindesteffiziente Betriebsgröße und ein hohes Maß an Gründungen gekennzeichnet sind. Regionales Wachstum hat einen deutlich positiven Einfluss, während sich für die nationale Entwicklung der betreffenden Branche eher ein negativer Zusammenhang mit den Überlebens-chancen zeigt. In den Analysen ergibt sich ein bemerkenswert hohes Maß an räumlicher Autokorrelation.
Keywords: D21; L10; M13; R10; 330; New-firm survival; hazard; entry; market selection; Überleben von Gründungen; Hazard; Marktzutritt; Marktselektion